The Influence of Profitability and Cash Holding on Income Smoothing in an Islamic Perspective - Nasiatul Hana Fikriyah; N. Nurlaili; Ersi Sisdianto (Manunggal Halim Jaya, 2026)
This study aims to analyze the effect of profitability and cash holdings on income smoothing from an Islamic perspective in Islamic commercial banks in Indonesia from 2020 to 2023. The sampling technique used was purposive sampling with 10 Islamic commercial banks in Indonesia over 4 years. This study used a quantitative approach using logistic regression. The model testing uses the Hosmer and Lemeshow model goodness-of-fit test, the coefficient of determination test, and the partial and simultaneous significance tests. The study's results indicate that, partially, profitability and cash holdings do not influence income smoothing, as evidenced by the significance values of each variable being greater than 0.05. However, simultaneously, both variables influence income smoothing. From an Islamic perspective, the results of this study indicate that Islamic commercial banks are committed to the principles of transparency, honesty, and accountability in financial reporting. This study found no indication that Islamic bank management smokes income based on profitability or cash holdings. This study expands the literature on Islamic accounting by emphasizing the importance of ethical and responsible profit management and providing an overview of how Islamic principles are applied in current financial practices.